Zeros and shared one value of q-shift difference polynomials - Q. Zhao; J. Zhang (Հայաստանի ԳԱԱ)
In this paper, we investigate uniqueness problems and zero distributions of q-shift difference polynomials of meromorphic functions with zero order in the complex plane. The obtained results extend some previous known results.
Keywords: Mathematics; Science